FIRE DANGER IN THE SUPPLY AREAS OF HYDROELECTRIC RESERVOIRS UNDER THE RESTORATION PROCESS IN THE SOUTH OF MINAS GERAIS, BRAZIL - Fillipe Tamiozzo Pereira Torres; Shauanne Dias Pancieri; Vicente Paulo Santana Neto; Vinicius Barros Rodrigues (Revista Árvore, 2024)
ABSTRACT The partial or complete loss of vegetation cover triggers an increase in surface runoff, erosion, and sedimentation of water bodies, including reservoirs for hydroelectric power generation, reducing their life expectancy. To control or mitigate this issue, ecological restoration interventions should prioritize the recovery of areas most vulnerable to these processes, such as springs. Conversely, wildfires cause damage to vegetation cover and hinder ecological restoration and/or natural regeneration processes. Therefore, this study aimed to identify - with the aid of Geographic Information Systems - the temporal and spatial likelihood of fire occurrences in spring recharge areas undergoing ecological restoration and contributing to hydroelectric reservoirs in southern Minas Gerais, Brazil. The findings indicated that the months with the highest probability of wildfire occurrences were August and September (accounting for 66% of cases), requiring increased attention to prevention efforts. Furthermore, locations most susceptible to fires (steeper slopes, more flammable vegetation, and higher anthropogenic use) should be treated as priorities for both prevention and ecological restoration actions.